MODERN APPROACHES IN THE TREATMENT OF OSTEOARTHRITIS OF THE KNEE - Adamović, Ana (PONS - medicinski časopis, 2024)
Introduction. Arthrosis is a common, primarily non-inflammatory, chronic, slowly progressing disease of the joints, with the most common localization in the knee joint, which is the main cause of chronic disability. As there is still no treatment that can stop the process of joint degeneration, we can only come up with measures to reduce pain and improve the functionality and quality of life of the patient. The aim of this study is to present recommendations for the treatment of gonarthrosis, with special reference to procedures applied at the level of primary health care. Method and material. The research was designed as a review paper. Based on keywords, various databases were reviewed, as well as recommendations from domestic and international rheumatology societies. Results and discussion. According to the Brussels Declaration on Rheumatic and Musculoskeletal Diseases (RMD), these diseases affect more than a quarter of people in Europe. The frequency increases with age, especially in black and yellow females, but it does not have to be an inevitable consequence of aging. The treatment plan for patients with osteoarthritis involves the application of mutually complementary individual measures. The best indicator of the severity of the disease is the presence of pain, so pain treatment is the most important part of the therapy. Treatment can be non-surgical or surgical. Non-surgical is divided into non-pharmacological and pharmacological treatment. Weight loss is the main therapeutic goal. Education includes group counseling which encompasses coping with the disease, self-control, self-help, and a structured exercise program. Pharmacological measures include the use of analgesics and antirheumatic drugs. Protheses, orthotics and a walking stick are recommended aids. Physical procedures: ultrasound, kinesiotherapy, interference currents... Biological therapy is applied according to special protocols. Total arthroplasty is the last therapeutic option. Conclusion. In addition to the prevention of osteoarthritis of the knee, the most important is the application of basic non-pharmacological measures with an emphasis on educating patients and their family members about the disease, self-help, dosage, regular physical exercise and weight reduction. What is most realistically possible to implement in primary health care is to increase the use of non-pharmacological forms of treatment such as weight reduction and regular exercise. The task of the entire society is to raise awareness of degenerative joint diseases and their public health significance, as well as the promotion of healthy lifestyles.